Wpływ materii organicznej na zmiany rozpuszczalności metali ciężkich w glebach zanieczyszczonych w świetle literatury = Influence of organic matter on the solubility of heavy metals in contaminated soils - a review of literature - Cuske, Mateusz; Karczewska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents a critical review of literature focused on the influence of organic matter on the changes in solubility of heavy metals in contaminated soils. Various kinds of organic matter are commonly used in remediation processes in order to increase soil sorption capacity and to immobilize heavy metals.
Keywords: miedź; mobilizacja; immobilizacja; węgiel brunatny; nawóz organiczny; osady organiczne; komposty; biowęgiel; ściółka; rozpuszczalny węgiel organiczny; copper; mobilization; immobilization; brown coal (lignite); organic fertilizer; sewage sludge; composts; biochar; forest litter; dissolved organic carbon